Restructuring the Emergency Department during the COVID pandemic - Grande Ratti, María Florencia; Martinez, Bernardo (Revista del Hospital Italiano de Buenos Aires, 2022)
As a result of this publication, we take the opportunity to share the effect that COVID-19 had on the Emergency Department, in terms of number of consultations, reasons and their characteristics; and we also share with you about our experience in the necessary restructuring during the pandemic: planning, organization, structure and coordinated procedures.